USAHA-USAHA GURU UNTUK MEMBANGKITKAN MOTIVASI BELAJAR SEJARAH BAGI SISWA SMA: STUDI KASUS DI SMA NEGERI 2 TEMANGGUNG DAN SMA INSTITUT INDONESIA SEMARANG - Oktaviani, Yuliyen (Paramita: Historical Studies Journal, 2011)
The main problem examined in this study is the extent to which high school students interest in the subjects of history, learning how to develop design, application of learning methods to enhance motivation, and constraints in the teaching of history in the SMA Negeri 2 Temanggung and SMA Institut Indonesia Semarang. This study uses qualitative methods. Informants in the study are history teachers, students and the school. Data collection techniques done with interviews, observation and questionnaire. The results of this study indicate that the interest of students to study history at the SMA Negeri 2 Temanggung is about 40% and in SMA Indonesia Institute Semarang approximately 48%. The teachers in both high school also has developed a learning design that is used in teaching as Learning Implementation Plan, syllabus and other composition which is made in accordance with that determined by the Department of Education and Teachers Council made in Subjects. In addition, teachers in both high school still apply methods of lectures, but also have varied with other teaching methods such as discussion method, instruction method using an interactive CD as well as field trips. ÃÂ Keywords: Motivation, Learning history ÃÂ